MEMAHAMI PELAYANAN KESEHATAN YANG DAPAT DIBERIKAN OLEH PERAWAT PRAKTIK MANDIRI BERDASARKAN UNDANG-UNDANG NO 38 TAHUN 2014 TENTANG KEPERAWATAN - Gunawan Widjaja; Siti Hafifa Marlinda Putri (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2022)
The Nursing Act recognizes different types of nurses with various competencies, but not much is known. This paper aims to provide an understanding of nurses who run independent practice. This research is a research with a qualitative approach based on norms. The findings and discussion show that in principle, nurses who carry out independent practice must have competence as a nursing profession with various specialties. One of them is that independent nurses are required to be independently responsible for each nursing care carried out by them